(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The critical analyses of thevarious representations of the partition violence attempted in the preceding sectionclearly reveal in the obsessive nature of the event of vivisection of India in1947. The event and the concomitant unprecedented carnage witnessed by thesubcontinent came as a shockingly ironic reward of the united fight forfreedom. The partition fiction, therefore, is a brutally realistic account ofthe blood curdling violence. However, it would be injudicious toinfer that the partition novels considered in the study are mere stories of theharrowing incidents of violence. Instead, they are, in essence, discerninginsights into the complex human nature. What Harish Raizada observes ofKhushwant Singh is equally true of all other Indo-English novelists whosefiction has treated the holocaust of partition, Raijada writes that KhushwantSingh turned to fiction “to let out his disenchantment with the long-cherishedhuman values in the wake of inhuman bestial horrors and insane savage killingson both sides during the partition of the sub-continent between India andPakistan in August 1947....”1